Molecular phyloecology suggests a trophic shift concurrent with the evolution of the first birds - Wu, Yonghua (Communications biology, 2021)
Birds are characterized by evolutionary specializations of both locomotion (e.g., flapping flight) and digestive system (toothless, crop, and gizzard), while the potential selection pressures responsible for these evolutionary specializations remain unclear. Here we used a recently developed molecular phyloecological method to reconstruct the diets of the ancestral archosaur and of the common ancestor of living birds (CALB). Our results suggest a trophic shift from carnivory to herbivory (fruit, seed, and/or nut eater) at the archosaur-to-bird transition. The evolutionary shift of the CALB to herbivory may have essentially made them become a low-level consumer and, consequently, subject to relatively high predation risk from potential predators such as gliding non-avian maniraptorans, from which birds descended. Under the relatively high predation pressure, ancestral birds with gliding capability may have then evolved not only flapping flight as a possible anti-predator strategy against gliding predatory non-avian maniraptorans but also the specialized digestive system as an evolutionary tradeoff of maximizing foraging efficiency and minimizing predation risk. Our results suggest that the powered flight and specialized digestive system of birds may have evolved as a result of their tropic shift-associated predation pressure. Yonghua Wu applies recently developed molecular phyloecological methods to identify a trophic shift from carnivory to herbivory in the earliest birds. Predation pressure from becoming low-level consumers may have stimulated the evolution of powered flight as an anti-predator strategy against gliding predatory non-avian maniraptorans.